Notary/PPAT Responsibility for Misuse of Tax Fund Custody by Parties - Lutfiah, Putri Hijrotul; Cahyandari, Dewi; Rahmat Sjafi'i, Imam (The Islamic Education and Multiculturalism Foundation, 2024)
In recent decades, many notaries/PPATs have been involved in legal issues, both intentionally and unintentionally. One problem that often occurs is the abuse of trust related to land rights tax payments entrusted by service users to notaries/PPATs. There is no regulation that allows notaries to pay tax for taxpayers, so the entrustment of tax money to notaries is only based on trust. The deposit of tax money is considered an additional service by notaries, even though there is no specific legality governing it. As a result, this practice is often practiced by notaries/PPATs. The deposit of tax money gives rise to both criminal and civil rights and obligations of the notary. If notaries fail to pay the deposited tax, they may be criminally prosecuted for fraud or embezzlement, or civilly sued, depending on whether the act is unlawful or constitutes a default. The type of research used in this study is Normative legal research, Attributive power is often described by the legal division of state power, and delegated power is the power resulting from the delegation of attributive authority, while delegation does not involve the delegation of authority. matters relating to the authority and power obtained by the Notary/PPAT over the tax deposits submitted by the Clients for the payment of PPH and BPHTB and not all Notaries/PPATs exercise the power/authority properly, this is of course a problem, therefore in this finding the prevention of the power/authority granted is discussed. The short conclusion is that Notaries/PPATs who commit tax evasion and abuse must be responsible for their own actions, because this violates the code of ethics which requires notaries to act honestly and responsibly. Honesty, ethics, and good morals are very important in carrying out notary duties, because the public can recognize a notary office that is ethical and moral.